Irregular Migrations in Southeast Asia: Challenges for Protection and Migration - Basir, Salawati Mat (UI Scholars Hub, 2020)
The region of Southeast Asia is extremely diverse in terms of culture, language, ethnicity, economic development, forms of government and degrees of political freedom. Migration of all types has played and continues to play a crucial role in the political economy of the region and is central to the contemporary economies of all of the states within it. In terms of protection and migration policy analyses, Southeast Asia is often folded into the larger ‘regions’ of Asia, the Asia-Pacific, or a hybrid sub-region consisting of East and Southeast Asia, depending on the type of migration, and the policy issues under consideration Given the diversity of migration dynamics in Southeast Asia that could be considered within this paper, this article focus primarily on challenges for protection and policies concerning irregular migration, both because of the growing economic importance and political impact of irregular migration.